The last Romantics: Kipling and Yeats, a comparative biography 1865-1906 - Bubb, ABT (2014)
My thesis examines Kipling and Yeats within the structure of a ‘comparative biography’. My premise is that reading these two near-exact contemporaries alongside one another yields remarkable discursive echoes. My method consists in identifying these mutual echoes in their poetry and political rhetoric, and charting them against synchronicities in their lives. By reading one author against another in a fashion that might be considered canonically incongruous, I seek to throw light on unacknowledged links running across the cultural nexus of the period. I find these echoes particularly intriguing since Kipling and Yeats were for most of their careers irreconcilable political enemies. Yeats in his political ascendance frequently played to the gallery by denouncing Kipling, while the latter hardly varnished his opinion of Irish poetry and Irish nationalism. However, a cross-reading of the two poets’ bardic ambitions, heroic tropes and interpretations of history reveals that they frequently partake of a common discourse to achieve their opposed political ends. After supplementing this analysis with a biographical perspective, we can perceive that these discourses originate in their late 19th century artistic upbringing, and in the closely linked social circles which they inhabited in fin-de-siècle London. It is their very mutuality during the 1890s which imparts rancour to their twentieth-century attitudes, after the Boer War had ideologically sundered them. Throughout, the thesis conceives them as figures transiting through both space and period. They had to reject but also adapt their Victorian inheritance in order to carry forward the Romantic poetic. Simultaneously, they undertook a physical transition between the colonial or semi-colonial societies of their birth and the metropolitan arena of their celebrity and influence. I see them as hybrid personalities and as romantic intellects, bringing imaginative fire from the colonial margins to satisfy the orientalist curiosity, and to soothe the fin-de-siècle anxieties, of the imperial centre. Although these peregrinations lead to a juggling of identities and poetic masks, in this dynamic lay both their success as authors and their influence as political and prophetic figures.